2018
DOI: 10.1002/jcad.12175
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social–Emotional Mediators on Middle School Students’ Academic Growth as Fostered by an Evidence‐Based Intervention

Abstract: The authors describe a school counselor intervention delivered to a predominantly Hispanic group of 193 7th‐grade students. Using multilevel modeling, the authors found that participation resulted in greater rates of academic achievement, particularly in math and for students who pretested at lower achievement levels. Results indicated an indirect effect on math achievement for the executive functioning constructs of plan and organize and task completion, but no executive functioning mediators were found for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 64 publications
4
25
0
Order By: Relevance
“…The SSS program is a humanistically grounded school counseling intervention that supports students' development of cognitive, social, and self-management skills. Without changes in the current program structure, results from the current study remain consistent with other studies conducted with larger samples of general education students Lemberger et al, 2015Lemberger et al, , 2018: Exceptional students receiving special education services were found to experience positive effects on social and emotional learning skills, executive functioning constructs, and academic competency. However, observational data collected allude to activities in which exceptional students consistently became disengaged.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The SSS program is a humanistically grounded school counseling intervention that supports students' development of cognitive, social, and self-management skills. Without changes in the current program structure, results from the current study remain consistent with other studies conducted with larger samples of general education students Lemberger et al, 2015Lemberger et al, , 2018: Exceptional students receiving special education services were found to experience positive effects on social and emotional learning skills, executive functioning constructs, and academic competency. However, observational data collected allude to activities in which exceptional students consistently became disengaged.…”
Section: Resultssupporting
confidence: 87%
“…Previous studies on the SSS program have indicated a significant impact on executive functions Lemberger et al, 2015Lemberger et al, , 2018. Results from the current study remain consistent with past findings: Students experienced moderate differences in teacher-reported executive functioning ability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Past studies of the SSS curriculum using ASE‐influenced practices and outcomes evince strong support for the effects of the intervention on students' executive functioning, social skills, and academic achievement (e.g., Bowers, Lemberger, Jones, & Rogers, ; Lemberger, Carbonneau, Selig, & Bowers, ; Lemberger, Selig, Bowers, & Rogers, ). Although it might be inferred from the theoretical relatedness of the various SSS curricula that RTL should contribute to young students' development of executive function and social‐emotional learning, there are currently no studies that explicitly consider intervention effects for these important school outcomes.…”
Section: The Advocating Student‐within‐environment Approach To Schoolmentioning
confidence: 99%
“…social and emotional learning (SEL) and mindfulness-based interventions (MBIs) have been found to be effective interventions with young children, each resulting in a number of affective and cognitive gains (Greenberg & Harris, 2012;Zoogman, Goldberg, Hoyt, & Miller, 2015). For practitioners, there are conceptual and practice similarities between SEL and MBI activities that are consistent with the priorities of early childhood educators (Denham & Weissberg, 2004) and counselors of children (Bowers, Lemberger-Truelove, & Brigman, in press;Lemberger, Carbonneau, Selig, & Bowers, 2018).…”
mentioning
confidence: 99%